Beyond Tolerance: Understanding Cultural Recognition, Discrimination Awareness, and Social Harmony Among Multicultural University Students in Southeast Sulawesi, Indonesia - Hartini Hartini; Hendra Hendra; Erens E. Koodoh; Aghista Febriyani (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Indonesia's multicultural society, characterised by ethnic, linguistic, religious, and cultural plurality, presents both opportunities and challenges for social cohesion. University campuses, as microcosms of this diversity, serve as critical sites where young adults negotiate cultural identities, construct intergroup attitudes, and enact or contest practices of recognition and tolerance. Despite extensive scholarly attention to multiculturalism at the macro level, empirical evidence on how undergraduate students in eastern Indonesia subjectively experience and interpret cultural diversity remains limited. Objective: This study aims to explore students' conceptual understanding of multiculturalism, their attitudes toward cultural recognition and minority rights, patterns of intergroup interaction, awareness of prejudice and discrimination, and hopes for future social integration within a multicultural campus environment in Southeast Sulawesi, Indonesia. Methods: A qualitative phenomenological approach was employed. Semi-structured in-depth interviews were conducted with 16 purposively selected undergraduate students from six different departments at the Faculty of Humanities (Fakultas Ilmu Budaya), Halu Oleo University, Kendari, between December 2025 and January 2026. Participants represented diverse ethnic backgrounds including Tolaki, Muna, Buton, Bugis, and Wawonii. Data were collected across six thematic dimensions: (1) conceptual understanding of multiculturalism; (2) cultural recognition and minority rights; (3) social interaction and intergroup relations; (4) prejudice and discrimination; (5) future aspirations and social hope; and (6) personal and emotional experiences of cultural identity. Thematic analysis was applied to identify recurring patterns and divergent perspectives across informants. Results: Findings reveal that while most participants articulated a positive orientation toward cultural diversity viewing it primarily as a social resource rather than a threat their understanding of multiculturalism tended to remain anchored in tolerance as passive coexistence, rather than active recognition or structural inclusion. Participants from majority-Muslim, ethnically homogeneous home environments demonstrated lower sensitivity to minority experiences compared to those with direct exposure to cultural otherness. Subtle forms of discrimination, particularly verbal microaggressions and exclusionary language use, were widely reported yet frequently normalised as harmless humour. The role of education was consistently valorised, while government policy implementation was critiqued as inconsistent and insufficiently protective of indigenous and minority group rights. Social media was identified as a dual-edged force capable of both bridging and exacerbating cultural divisions. Participants broadly endorsed a vision of integration as 'unity in diversity' (Bhinneka Tunggal Ika), emphasising coexistence without cultural assimilation. Conclusions: The study underscores the need to move beyond tolerance-centred frameworks toward deeper engagement with recognition, equity, and structural justice in multicultural education. Campus environments in culturally diverse regions of Indonesia can serve as transformative spaces for intercultural learning, provided that curricula, institutional policies, and social norms actively affirm the value of minority identities. These findings contribute to the broader discourse on multiculturalism in postcolonial, multi-ethnic societies and offer grounded insights for educators, policymakers, and practitioners working to strengthen social cohesion in Southeast Sulawesi and comparable contexts. Keywords: cultural recognition; cultural diversity; minority rights; university students; Bhinneka Tunggal Ika